The American theatre reader : essays and conversations from American theatre magazine - Vogel, Paula (Theatre Communications Group, 2009)
In celebration of American Theatre's twenty-fifth anniversary, the editors of the nation's leading theater magazine have chosen their best essays and interviews to provide an intimate look at the people, plays, and events that have shaped the American theater over the past quarter-century. Over two hundred artists, critics, and theater professionals are gathered in this one-of-a-kind collection, from the visionaries who conceived of a diverse and thriving national theater community, to the practitioners who have made that dream a reality. The American Theatre Reader captures their wide-ranging stories in a single compelling volume, essential reading for theater professionals and theatergoers alike.